PENINGKATAN PENGETAHUAN TENTANG PENTINGNYA KESELAMATAN DAN KESEHATAN KERJA (K3) PADA TENAGA KERJA HOUSEKEEPINGDI HOTEL - Azila Rahimah Dalimunthe (Jurnal Kesehatan, 2024)
Occupational Safety and Health (OSH) is defined as science and its technical and technological application to prevent work accidents and work-related illnesses in every job performed. From a legal point of view, OSH can be interpreted as an effort to protect so that every worker and other person who enters the workplace is always healthy and safe and that production process resources can run safely, efficiently and productively. The main objective of implementing OSH based on Law number 1 of 1970 concerning Occupational Safety, namely protecting and guaranteeing the safety of every worker and other people in the workplace, guaranteeing that every source of production can be used safely and efficiently, and increasing national welfare and productivity. In OSH housekeeping, housekeeping is a part of the hotel that handles matters relating to beauty, tidiness, cleanliness, completeness of all rooms and all other public areas so that all guests and employees can feel safe and comfortable in the hotel. This means that the workforce of each department has a responsibility, therefore the hotel implements an OSH System to maintain the safety and health of the workforce and maintain hotel quality. The method used in this article is a qualitative method, namely data that is narrative in nature, not numbers, where the source of this data comes from various journal references to strengthen reading results.